Development and nutritional evaluation of crackers fortified with yellowstripe scad (Selaroides leptolepis) whole powder as a functional food for stunting prevention - Arista, Yuvita Lira Vesti; Noviyanti, Sri Handayani; Hutabarat, Michael Alexander; Mutamimah, Dewi; Moniz, Joana Paula Gerabella Da Cozta (Jurusan Teknologi Hasil Pertanian Universitas Mulawarman, 2026)
Yellowstripe Scad (Selaroides leptolepis) has potential as a fortificant to enhance the nutritional quality of crackers. The incorporation of yellowstripe scad whole fish powder not only improves the nutrient content but also reduces processing waste. Fish-based crackers can serve as dietary food products, nutrient-dense snack alternatives, and supplementary foods to support stunting prevention. This study aimed to evaluate the nutritional composition (moisture, lipid, dietary fiber, protein, and ash content) and physical quality (texture) of fish crackers. The experiment was designed using a Completely Randomized Design with a single factor, namely, the addition of yellowstripe scad whole powder (SFF) at six levels: 0, 3, 6, 9, 12, and 15%. The data obtained were analyzed using Analysis of Variance, followed by Duncan’s Multiple Range Test to determine significant differences. The results revealed that the addition of yellow stripe scad whole powder significantly affected (p<0.05) the physicochemical properties of the yellow stripe scad crackers. Crackers with 15% yellowstripe scad whole powder exhibited the highest protein, lipid, and ash contents of 18.5, 8.97, and 8.97%, respectively. Meanwhile, the addition of 3% yellowstripe scad whole powder produced crackers with the most desirable moisture content, dietary fiber, and texture characteristics of 3.59%, 3.87%, and 1,101 N/cm², respectively.